GENETIC IMPROVEMENT OF SOME BACTERIAL ISOLATESIN UTILIZATION OF HYDROCARBON COMPOUNDS - Al-Saffar, Ali; AL-Gelawi, Majed (Iraqi Journal of Science, 2024)
Six bacterial isolates belonging to the genus Pseudomonas wereselected for their high ability to utilize crude oil. These isolates showed adiverge ability for utilization of different hydrocarbon compounds and 2isolates (P. aeruginosa RB19 and Pseudomonas sp. RB29) were able toutilize all the tested compounds except tetrahydrofuran, sodium toluate andtrans–1, 2–diphenylethylene. Conjugation between P. aeruginosa RB19and P. aeruginosa RB27 was made in an attempt to obtain bacterialisolates, capable to utilize a wide range of hydrocarbon compounds. Theconjugation was successful and a number of transconjugants were obtained.All transconjugants were able to utilize sodium toluate, and some of thesetransconjugants were able to utilize salicylic acid. This indicated thatP. aeruginosa RB27 was the recipient bacterium which received pSR202plasmid (responsible for salicylic acid and benzoate utilization) fromP. aeruginosa RB19.